Crescimento, produção, trocas gasosas e qualidade pós colheita de Beta vulgaris L. em função de doses de ácido ascórbico e de lâminas de irrigação - Gonçalves, Anderson Carlos de Melo (2018)
Beet (Beta vulgaris L.) is a crop of increasing demand. However, the water availability factor is determinant in its production. Physiological strategies aimed at using the limited water resource more efficiently is indispensable, with the use of antioxidants such as ascorbic acid being an option. The objective of this study was to evaluate the growth, production, gas exchange and postharvest quality of Beta vulgaris L. in function of doses of ascorbic acid and irrigation slides. The experiment was conducted under a protected environment at the Centro de Ciências Agrárias, from the Universidade Federal da Paraíba, Areia, Paraíba, Brasil, in a randomized complete block design with five doses of ascorbic acid (0.00, 0.29, 1,00, 1.71 and 2.00 mM), and five irrigation slides (40.0, 51.6, 80.0, 108.4 and 120.0% of the evapotranspiration), combined according to the Central Compound of Box experimental matrix, totalizing nine treatments, with three replicates and three plants per plot. Growth, gas exchange, chlorophyll, fluorescence, production and post-harvest analyzes were performed. The data were submitted to analysis of variance, regression and the evaluations repeated in time by mixed model. Pearson correlation coefficients were estimated in the echophysiological variables. The doses of ascorbic acid in the largest irrigation slides did not express significance in growth, gas exchange, chlorophyll, fluorescence and production, only in postharvest quality. The larger irrigation slides increased production, however, they reduced correlating ecophysiological indexes. It was concluded that the growth and production of beets increase with the highest irrigation depths independently of the application of ascorbic acid, which influences the foliar mass alone. The ecophysiological correlations are significant. Doses of ascorbic acid in the smaller slides increase the post-harvest quality of beet.